Modeling and experiment study of hydraulically damped rubber mount under larger amplitude excitation at low frequency. (January 2023) - Liao, Xin; Chen, Lin; Wang, Hu; Pei, Xin
To improve the ride comfort of the cab of construction machinery and reduce the harm of vibration to the driver, a nonlinear lumped parameter model of passive hydraulic damping rubber mount (PHDRM) is first proposed. The nonlinearity of multi-inertial tracks is fully considered. Then, the global FE (finite element) fluid-solid coupling model of the isolator is developed in ABAQUS. The multi-field coupling solution and a joint simulation mode are employed in this paper. Meanwhile, the rubber element and inertial track parameters are identified respectively. Finally, multiple sets of dynamic performance experiments are performed on the different PHDRM samples. The experiment results indicate that the simulation results for two modeling methods of the vibration isolation system are consistent with the experimental datum. The modeling approaches have both reliability and accuracy under larger amplitude excitation at low frequency. Furthermore, the effects of different rubber elements and inertial track of PHDRM on low-frequency dynamic characteristics under larger amplitude are investigated and discussed, respectively. The experimental outcomes also provide a practical reference value for nonlinear modeling method research and dynamic performance analysis of PHDRM with complex structures further.